PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN MENJADI NASABAH PT. BANK NEGARA INDONESIA (PERSERO) TBK KANTOR CABANG PEMBANTU MARTAPURA - Rozi Sonjaya; Luis Marnisah; Fakhry Zamzam (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2021)
This research aims to obtain the results of an analysis of the influence of the marketing mix on the decision to become a customer of PT. Bank Negara Indonesia (Persero) Tbk Martapura Sub-Branch Offices partially and simultaneously. The research methods using quantitative and qualitative approaches, field data collection using questionnaire and interview techniques. The population in this study was 138 customers who opened a savings account at BNI KCP Martapura in April 2020 and samples were 138 respondents. Testing the data using the t test, that the product has no significant effect on the decision to become a customer with t count 1.901 < t table 1.978, price does not significantly influence the decision to become a customer with t count -0.507 < t table 1.978, promotion does not significantly influence the decision to become a customer with t count 1.826 < t table 1.978, place has a significant effect on the decision to become a customer with t count 3.790 > t table 1.978, people / bank officer have a significant effect on the decision to become a customer with t count 2.771 > t table 1.978, physical evidence do not have a significant effect on the decision to become a customer with t count 1.276 < t table 1.978 and the process has no significant effect on the decision to become a customer with t count 1.650 < t table 1.978. The F Test Results that the product, price, promotion, place, people / bank officer, physical evidence and process simultaneously have a significant effect on the decision to become a customer with an F count of 35.055 > F table 2.08. The results showed that the marketing mix variable that had the most significant effect on the decision to become a customer was the place variable. Strategies to increase the interest of prospective customers can be done by maintaining and improving strategic locations that are already owned and improving the skills and abilities of service personnel